Orgulho de ser leitor: uma análise discursiva do que enunciam jovens leitores sobre si e sobre a leitura em postagens na rede social SKOOB - Silva, Andrei Cezar da (Universidade Federal de São Carlos, 2022)
This work, as well as other research conducted by LIRE - Laboratório de Estudos da Leitura (CNPq-UFSCar), aims to analyze discourses on reading and to comprehend representations of this practice shared by different communities of readers. It is part of the project currently coordinated by our supervisor, entitled “Proud readers, ashamed readers: emotions in discourses on reading”, whose goal is to deduce, through the analysis of discourses on reading, the expression of emotions, also defined by the “order of discourse”, as regular forms of arguing, as a relatively protocol duty/power when talking about a particular practice or the subjects that undertake it. In this dissertation, we present the results of our research, which consisted in the survey, description and analysis of very peculiar statements: comments from young readers in which they expressed “pride” of reading, pride of being a reader. To do this, we constituted a corpus of statements from posts by young internet users registered in the social network SKOOB, self-declared as the “largest social network of readers in Brazil”. In their comments about works already read or that they still intend to read, they present evaluations of the works, authors and genres, establish relationships with other readers, and talk about themselves as readers. What is enunciated about reading in these posts interests us to the extent that what is enunciated echoes consensual collective representations that these young people, as well as all of us, subjects of the same time and space, share about this practice. From the analysis of what these young people say, we deduce the ways they use to present/recognize themselves as readers and what discourses about reading these forms of self-representation go back to, focusing on those statements in which there is the enunciation, direct or indirect, of “pride” (or pride as its effect) related to the reading condition. In order to identify probable continuities and/or discontinuities in the discourses about reading that circulate among us today, as well as to describe regularities and variations in the representations of “pride” regarding this practice, among this specific segment of the reading public, we subsidize our analysis on principles of Discourse Analysis, the Cultural History of reading and the History of sensibilities/emotions. As we have observed, the forms of enunciation of juvenile reader “pride” respond to certain historically validated and hegemonic reading protocols about the reading condition. Among the forms of expression of reading-related 'pride', one of them concerns the actualization of the representation that to be a reader is to read a lot and always, be it the same work, repeatedly, or several distinct works, simultaneously and sequentially.
Pride of being a reader: a discursive analysis of what young readers enunciate about themselves and about reading in posts at the social network SKOOB
Keywords: Discursos sobre a leitura; Jovens leitores; Emoções sobre a leitura; Rede Social SKOOB; Orgulho de ser leitor; Discourses on reading; Young readers; Emotions about reading; Social network SKOOB; Pride of being a reader; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::TEORIA E ANALISE LINGUISTICA